Constitutional and Judicial Verification of International and Interstate Agreements - B. A. Ossipian (Московский журнал международного права)
The activity of Constitutional Court of the Russian Federation on verification of constitutionality of international agreements has great significance for optimization of the process of proper implementation of international law obligations by the Russian Government. Constitutional and judicial verification of the practice for conclusion and realization of interstate agreements enables Russia to fortify the constitutional foundations of the further development of its general and, particularly, federative development.To verify in timely and proper manner international agreements and treaties the Constitutional Court of RF, being independent and responsible branch of State power, has to be empowered to exercise its own initiative for the verification of constitutionality thereof. Therefore, the Constitutional Court of RF has to be given an additional opportunity to control constitutionality of already acting international agreements and the process of their realization either. To put it in other words, the conclusion of the Constitutional Court of RF on constitutionality of the practice of concluding, implementing, changing and termination of international treaties must be obligatory.In the process of verification of interstate (federative) agreements the Constitutional Court of RF is to obliged to consider the aims and requirements of Article 5 of the Constitution of Russian Federation on the right of peoples on self-determination, in particular, to guarantee the freedom of cultural development of the national subjects of the Russian Federation, and to prohibit the possibility of voluntary changing of the status and unconstitutional redistribution of there prerogatives by administrative methods. Insurance of the balance of the lawful and constitutional interests of federal and regional bodies of State power should become the main direction in activity of the Constitutional Court of the Russian Federation.